Overweight and obesity among children: a relationship between maternal beliefs and feeding practices with children's body mass index-for-age in bandar and Jugra Kuala Langat Selangor - Aslan, Asrawati Awalina; Sulaiman, Norhasmah (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2020)
Introduction: Childhood obesity is one of the major public concerns as prevalence was showing an increasing trend in Malaysia. This study aimed to determine the associations between maternal beliefs, attitudes and feeding practices with children’s Body Mass Index-for-age (BMI-for-age). Method: A cross-sectional study was carried out in Bandar and Jugra, Kuala Langat, Selangor in two-phase. The first phase was conducted to determine the prevalence of children’s body weight status involving 209 pairs of mothers and children. The second phase of the study aims to determine the socio-demographic characteristics, maternal beliefs, maternal attitudes and feeding practices with childhood obesity involving 148 pairs of mothers and children whose BMI-for-age are normal, overweight and obese only. A set of self-administered questionnaire was answered by the mothers and anthropometric measurements of children were taken. Results: Overall, about 24.9% of the children were overweight and obese. Maternal employment status (X2 = 9.135, p<0.05), perceived child weight status (r=0.267, p<0.05) and food restriction (r=0.186, p<0.05) were positively correlated with children’s BMI-for-age. The pressure to eat (r= -0.177, p<0.05) was negatively associated with children’s BMI-for-age. From multiple linear regression, maternal employment status, perceived child weight status and pressure to eat was shown to be factors associated with children’s BMI-for-age. Conclusion: In conclusion, the findings showed that maternal employment status, perceived on child weight status, restriction on food and pressure to eat were linked to children’s BMI-for-age. Therefore, mothers should be educated on appropriate feeding practices to help to maintain healthy BMI-for-age among younger children.